On the Starlikeness for Certain Analytic Functions - Guo, Lifeng; Wang, Yunhua; Liu, Jinzi (International Journal of Mathematical Research, 2013)
Let f(z) be an analytic function in the open unit disk U normalized with f (0)=0 and f’(0)=1. In this paper, the starlikeness for f(z) is discussed